High-tensile electrolytic copper foil and production process thereof

By adding specific additives to the electrolytic copper foil and electrolyzing the foil, the problem of insufficient tensile strength and apparent quality of the electrolytic copper foil is solved, high tensile performance and smooth appearance are achieved, and the quality and quality of the electrolytic copper foil are improved.

CN119640346APending Publication Date: 2025-03-18广东嘉元时代新能源材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411804595.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The tensile strength and apparent quality of existing electrolytic copper foils affect their quality and quality.

Method used

High tensile electrolytic copper foil is prepared by adding an aqueous solution containing an apparent improvement agent, a nonionic surfactant, a smoothing agent and gelatin as an electrolytic additive, and evenly dispersed, electrolytic foil is prepared, and anti-oxidation treatment, edge cutting and slicing packaging is performed to the electrolyte solution.

Benefits of technology

The excellent tensile resistance of electrolytic copper foil is achieved, and the synergistic effect of the apparent improvement agent and the smoothing agent is improved, effectively ensuring the quality and quality of the electrolytic copper foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178865170000071
    Figure BDA0005178865170000071
Patent Text Reader

Abstract

The invention relates to the technical field of electrolytic copper foils, in particular to a high-tensile electrolytic copper foil and a production process thereof. The appearance improving agent can form a molecular layer on the cathode, so that copper ions are deposited without orientation preference, fine and uniform crystal grains are obtained, and the surface of the produced electrolytic copper foil is brighter and more glossy. Furthermore, the smoothing agent can promote copper ions in the electrolyte to be more uniformly deposited on the cathode, so that the probability of copper stacking is effectively reduced, finally, the surface of the produced electrolytic copper foil is smoother, the roughness of the surface of the electrolytic copper foil is effectively reduced, and the electrolytic copper foil has better glossiness and appearance; under the action of mutual cooperation and mutual cooperation of the appearance improving agent and the smoothing agent, the prepared electrolytic copper not only has excellent tensile property, but also is smoother, smoother and glossy in appearance, and the quality of the produced electrolytic copper foil is effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrolytic copper foil, in particular to a high-tensile-strength electrolytic copper foil and a production process thereof. Background Art

[0002] Electrolytic copper foil is an important material for copper clad laminate (CCL), printed circuit board (PCB), and lithium-ion battery manufacturing. In today's rapidly developing electronic information industry, electrolytic copper foil is called the "neural network" for signal and power transmission and communication of electronic products. Electrolytic copper foil has been mainly used in construction since its birth. In my country, electrolytic copper foil is the main material for producing copper clad laminate, which is the main material for making printed circuit boards. Electrolytic copper foil is still the best conductive material for printed circuit boards. In addition, electrolytic copper foil can also be used for shielding cables and military facilities, composite materials used in buildings to prevent plant roots and waterproofing, conductive busbars for soft connections, pads in the machinery industry, and furniture decoration.

[0003] A method for preparing electrolytic copper foil is disclosed in the patent document with application number "CN201910335218.5". Although the technical solution proposed can effectively solve the abnormal problems such as oxidation color difference and edge tearing of the cathode roller surface, the tensile strength and apparent quality of the prepared electrolytic copper foil are relatively insufficient, which affects its quality to a certain extent. Based on this, the present invention provides a high-tensile electrolytic copper foil and its production process to solve the above-mentioned technical problems! Summary of the invention

[0004] The purpose of the present invention is to provide a high-tensile-strength electrolytic copper foil and a production process thereof. Under the synergistic and coordinated effects of a surface improving agent and a smoothing agent, the electrolytic copper prepared by the present invention not only has excellent tensile properties, but more importantly, its appearance is smoother, flatter and more shiny, which effectively guarantees the quality of the produced electrolytic copper foil.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a production process for high tensile strength electrolytic copper foil, comprising the following steps: placing an electrolyte at 50 to 60° C. in an anode tank, then adding an electrolytic additive, and performing electrolytic foil making after uniform dispersion; the copper foil obtained after electrolysis is sequentially subjected to anti-oxidation treatment, trimming, slitting and packaging to obtain a high tensile strength electrolytic copper foil.

[0007] Furthermore, the copper ion concentration in the electrolyte is 80-110 g / L, the H2SO4 concentration is 100-130 g / L, and the chloride ion concentration is 20-30 ppm.

[0008] Furthermore, the current density during electrolytic foil making is 50 to 80 A / dm2 , the electrodeposition time is 100 to 180 s.

[0009] Furthermore, the additive is an aqueous solution containing a surface improver, a non-ionic surfactant, a smoothing agent and gelatin, wherein the concentration of the surface improver in the aqueous solution is 0.6-1 g / L, the concentration of the non-ionic surfactant is 0.2-0.4 g / L, the concentration of the smoothing agent is 0.4-0.6 g / L, the concentration of the gelatin is 1.5-2 g / L, and the number average molecular weight of the gelatin is 1000-5000.

[0010] Furthermore, the nonionic surfactant is selected from any one of the nonionic fluorinated surfactant F-6000 and the nonionic fluorinated surfactant FS-104.

[0011] Furthermore, the flow rate of the electrolyte during electrolytic foil making is 30 to 40 m 3 / h, and the flow rate of the additive is 40-60mL / min.

[0012] Furthermore, the preparation method of the appearance improving agent comprises the following steps: adding 3-ethoxy-4-hydroxybenzaldehyde into a 15-20wt% ethanol aqueous solution at a dosage ratio of 0.03-0.05g / mL, mixing and stirring evenly, heating to 40-60°C, then slowly dripping a reducing agent therein, heating to 80-85°C after uniform dispersion, and stirring and reacting at this temperature for 8-12h; after the reaction is completed, slowly dripping a cyclohexanehexol phosphate aqueous solution with a mass of 85-95% of 3-ethoxy-4-hydroxybenzaldehyde and a concentration of 20-40wt% into the resulting component, mixing evenly, heating to 75-85°C, and naturally cooling to room temperature after thermal insulation for 3-5h, thereby obtaining the appearance improving agent.

[0013] Furthermore, the reducing agent is a saturated aqueous solution of sodium sulfite, and its usage is 75-85% of the mass of 3-ethoxy-4-hydroxybenzaldehyde.

[0014] Furthermore, the preparation method of the smoothing agent comprises the following steps:

[0015] Step 1, placing a 2-3 mol / L 1,3-diaminoheterocyclopentadiene aqueous solution in a constant temperature water bath at 50-60° C., adding 1,6-di(2,3-epoxypropoxy)hexane in a molar amount of 0.7-1.0 times that of 1,3-diaminoheterocyclopentadiene dropwise therein while stirring, mixing and stirring for 30-40 minutes, then heating to 90-95° C., and keeping the temperature at this temperature for reaction for 15-25 hours;

[0016] Step 2: After the reaction is completed, the reaction product is naturally cooled to 55-70° C., 1,2-oxathiohydroxyalkane-2,2-dioxide with a molar amount of 0.1-0.2 times that of 1,3-diaminocyclopentadiene is added, and the mixture is stirred and kept warm at 60-70° C. for 5-8 hours; after the reaction is completed, the resultant components are naturally cooled to room temperature, and then the pH is adjusted to 2.3-2.8 with 40-50wt% sulfuric acid, and the final product is a smoothing agent.

[0017] In a second aspect, the present invention provides a high tensile strength electrolytic copper foil, which is produced by the production process described above.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention uses 3-ethoxy-4-hydroxybenzaldehyde, a saturated aqueous solution of sodium sulfite, and an aqueous solution of cyclohexanehexol phosphate as raw materials, and finally prepares a surface improvement agent through a chemical reaction. The obtained surface improvement agent can form a molecular layer at the cathode, so that copper ions are deposited without orientation preference, thereby obtaining fine and uniform grains, and the surface of the produced electrolytic copper foil is brighter and glossier. Furthermore, the present invention uses an aqueous solution of 1,3-diaminoheterocyclopentadiene, 1,6-di(2,3-epoxypropoxy)hexane, and 1,2-oxathiohydroxyalkane-2,2-dioxide as raw materials, and prepares a smoothing agent through a chemical reaction. The prepared smoothing agent can promote the copper ions in the electrolyte to be deposited more evenly at the cathode, effectively reducing the probability of copper stacking, and finally making the surface of the produced electrolytic copper foil smoother and flatter, effectively reducing the roughness of the surface of the electrolytic copper foil, so that it has better gloss and appearance. Under the synergistic and coordinated effects of the surface improver and the smoothing agent, the electrolytic copper prepared by the present invention not only has excellent tensile properties, but more importantly, its appearance is smoother, flatter and more shiny, which effectively guarantees the quality of the produced electrolytic copper foil. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] A production process of high tensile electrolytic copper foil, comprising the following steps: placing an electrolyte at 50°C in an anode tank, then adding an electrolytic additive, and performing electrolytic foil making after uniform dispersion; the copper foil obtained after electrolysis is subjected to anti-oxidation treatment, trimming, slitting and packaging in sequence to obtain a high tensile electrolytic copper foil;

[0023] The copper ion concentration in the electrolyte is 80g / L, the H2SO4 concentration is 100g / L, and the chloride ion concentration is 20ppm; the current density during electrolytic foil making is 50A / dm 2 The electrodeposition time is 100s; the flow rate of the electrolyte during electrolytic foil making is 30m 3 / h, and the flow rate of the additive is 40mL / min.

[0024] The additive is an aqueous solution containing a surface improver, a nonionic surfactant, a smoothing agent and gelatin. The concentration of the surface improver in the aqueous solution is 0.6 g / L, the concentration of the nonionic fluorosurfactant F-6000 is 0.2 g / L, the concentration of the smoothing agent is 0.4 g / L, the concentration of the gelatin is 1.5 g / L, and the number average molecular weight of the gelatin is 1000.

[0025] The preparation method of the appearance improving agent comprises the following steps: adding 3-ethoxy-4-hydroxybenzaldehyde into a 15wt% ethanol aqueous solution at a dosage ratio of 0.03g / mL, mixing and stirring evenly, heating to 40°C, then slowly dropping a reducing agent therein, heating to 80°C after uniform dispersion, and reacting at this temperature for 8h under heat preservation and stirring; after the reaction is completed, slowly dropping a cyclohexanehexol phosphate aqueous solution with a mass of 85% of 3-ethoxy-4-hydroxybenzaldehyde and a concentration of 20wt% into the obtained product components, mixing evenly, heating to 75°C, heat preservation and reaction for 3h, and naturally cooling to room temperature to obtain the appearance improving agent; wherein the reducing agent is a saturated aqueous solution of sodium sulfite, and its dosage is 75% of the mass of 3-ethoxy-4-hydroxybenzaldehyde.

[0026] The preparation method of the smoothing agent comprises the following steps:

[0027] Step 1: Place a 2 mol / L 1,3-diaminoheterocyclopentadiene aqueous solution in a constant temperature water bath at 50°C, add 1,6-di(2,3-epoxypropoxy)hexane in a molar amount of 0.7 times that of 1,3-diaminoheterocyclopentadiene dropwise therein while stirring, mix and stir for 30 minutes, then heat to 90°C, and keep at this temperature for reaction for 15 hours;

[0028] Step 2: After the reaction is completed, the reaction product is naturally cooled to 55° C., 1,2-oxathiohydroxyalkane-2,2-dioxide with a molar amount of 0.1 times that of 1,3-diaminoheterocyclopentadiene is added, and the mixture is stirred and reacted at 60° C. for 5 hours; after the reaction is completed, the resultant components are naturally cooled to room temperature, and then the pH is adjusted to 2.3 with 40wt% sulfuric acid, and the final product is a smoothing agent.

[0029] Example 2

[0030] A production process of high tensile electrolytic copper foil, comprising the following steps: placing an electrolyte at 55°C in an anode tank, then adding an electrolytic additive, and performing electrolytic foil making after uniform dispersion; the copper foil obtained after electrolysis is subjected to anti-oxidation treatment, trimming, slitting and packaging in sequence to obtain a high tensile electrolytic copper foil;

[0031] The copper ion concentration in the electrolyte is 100g / L, the H2SO4 concentration is 120g / L, and the chloride ion concentration is 25ppm; the current density during electrolytic foil making is 60A / dm 2 The electrodeposition time is 150s; the flow rate of the electrolyte during electrolytic foil making is 35m 3 / h, and the flow rate of the additive is 50mL / min.

[0032] The additive is an aqueous solution containing a surface improver, a nonionic surfactant, a smoothing agent and gelatin. The concentration of the surface improver in the aqueous solution is 0.8 g / L, the concentration of the nonionic fluorinated surfactant FS-104 is 0.3 g / L, the concentration of the smoothing agent is 0.5 g / L, the concentration of the gelatin is 1.8 g / L, and the number average molecular weight of the gelatin is 3000.

[0033] The preparation method of the appearance improving agent comprises the following steps: adding 3-ethoxy-4-hydroxybenzaldehyde into a 15wt% ethanol aqueous solution at a dosage ratio of 0.04g / mL, mixing and stirring evenly, heating to 50°C, then slowly dropping a reducing agent therein, heating to 80°C after uniform dispersion, and reacting at this temperature with heat preservation and stirring for 10h; after the reaction is completed, slowly dropping a cyclohexanehexol phosphate aqueous solution with a mass of 90% of 3-ethoxy-4-hydroxybenzaldehyde and a concentration of 30wt% into the obtained product components, mixing evenly, heating to 80°C, heat preservation and reaction for 4h, and naturally cooling to room temperature to obtain the appearance improving agent; wherein the reducing agent is a saturated aqueous solution of sodium sulfite, and its dosage is 80% of the mass of 3-ethoxy-4-hydroxybenzaldehyde.

[0034] The preparation method of the smoothing agent comprises the following steps:

[0035] Step 1: Place a 2.5 mol / L 1,3-diaminoheterocyclopentadiene aqueous solution in a constant temperature water bath at 55°C, add 1,6-di(2,3-epoxypropoxy)hexane in a molar amount of 0.8 times that of 1,3-diaminoheterocyclopentadiene dropwise therein while stirring, mix and stir for 35 minutes, then heat to 90°C, and keep at this temperature for reaction for 20 hours;

[0036] Step 2: After the reaction is completed, the reaction product is naturally cooled to 60°C, 1,2-oxathiohydroxyalkane-2,2-dioxide with a molar amount of 0.15 times that of 1,3-diaminoheterocyclopentadiene is added, and the mixture is stirred and reacted at 65°C for 6 hours; after the reaction is completed, the resultant components are naturally cooled to room temperature, and then the pH is adjusted to 2.5 with 45wt% sulfuric acid, and the final product is a smoothing agent.

[0037] Example 3

[0038] A production process of high tensile electrolytic copper foil, comprising the following steps: placing an electrolyte at 60°C in an anode tank, then adding an electrolytic additive, and performing electrolytic foil making after uniform dispersion; the copper foil obtained after electrolysis is subjected to anti-oxidation treatment, trimming, slitting and packaging in sequence to obtain a high tensile electrolytic copper foil;

[0039] The copper ion concentration in the electrolyte is 110g / L, the H2SO4 concentration is 130g / L, and the chloride ion concentration is 30ppm; the current density during electrolytic foil making is 80A / dm 2 The electrodeposition time is 180s; the flow rate of the electrolyte during electrolytic foil making is 40m 3 / h, and the flow rate of the additive is 60mL / min.

[0040] The additive is an aqueous solution containing a surface improver, a nonionic surfactant, a smoothing agent and gelatin. The concentration of the surface improver in the aqueous solution is 1 g / L, the concentration of the nonionic fluorosurfactant F-6000 is 0.4 g / L, the concentration of the smoothing agent is 0.6 g / L, the concentration of the gelatin is 2 g / L, and the number average molecular weight of the gelatin is 5000.

[0041] The preparation method of the appearance improving agent comprises the following steps: adding 3-ethoxy-4-hydroxybenzaldehyde into a 20wt% ethanol aqueous solution at a dosage ratio of 0.05g / mL, mixing and stirring evenly, heating to 60°C, then slowly dropping a reducing agent therein, heating to 85°C after uniform dispersion, and reacting at this temperature with heat preservation and stirring for 12h; after the reaction is completed, slowly dropping a cyclohexanehexol phosphate aqueous solution with a mass of 95% of 3-ethoxy-4-hydroxybenzaldehyde and a concentration of 40wt% into the obtained product components, mixing evenly, heating to 85°C, heat preservation and reaction for 5h, and naturally cooling to room temperature to obtain the appearance improving agent; wherein the reducing agent is a saturated aqueous solution of sodium sulfite, and its dosage is 85% of the mass of 3-ethoxy-4-hydroxybenzaldehyde.

[0042] The preparation method of the smoothing agent comprises the following steps:

[0043] Step 1: Place a 3 mol / L aqueous solution of 1,3-diaminoheterocyclopentadiene in a constant temperature water bath at 60°C, add dropwise 1,6-di(2,3-epoxypropoxy)hexane in an amount equal to that of 1,3-diaminoheterocyclopentadiene while stirring, mix and stir for 40 minutes, then heat to 95°C and keep at this temperature for 25 hours;

[0044] Step 2: After the reaction is completed, the reaction product is naturally cooled to 70° C., 1,2-oxathiohydroxyalkane-2,2-dioxide with a molar amount of 0.2 times that of 1,3-diaminoheterocyclopentadiene is added, and the mixture is stirred and reacted at 70° C. for 8 hours; after the reaction is completed, the resultant components are naturally cooled to room temperature, and then the pH is adjusted to 2.8 with 50wt% sulfuric acid, and the final product is a smoothing agent.

[0045] Performance test: The relevant properties of the electrolytic copper foil samples provided in Examples 1 to 3 were tested respectively, and the test data obtained were recorded in the following table:

[0046]

[0047] By comparing and analyzing the relevant data in the table, it can be seen that under the synergistic and coordinated effects of the surface improver and the smoothing agent, the electrolytic copper prepared by the present invention not only has excellent tensile properties, but more importantly, its appearance is smoother, flatter and glossier, which effectively guarantees the quality of the produced electrolytic copper foil. This shows that the high tensile electrolytic copper foil and its production process provided by the present invention have a broader market prospect and are more suitable for promotion.

[0048] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0049] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A production process for high tensile strength electrolytic copper foil, characterized in that: The following steps are involved: The electrolyte at 50-60°C is placed in the anode tank, and then the electrolytic additive is added and evenly dispersed to produce the electrolytic foil; the copper foil obtained after the electrolysis is subjected to anti-oxidation treatment, trimming, slitting and packaging in turn to produce the high tensile electrolytic copper foil.

2. The production process of a high tensile strength electrolytic copper foil according to claim 1, characterized in that: The copper ion concentration in the electrolyte is 80-110 g / L, the H2SO4 concentration is 100-130 g / L, and the chloride ion concentration is 20-30 ppm.

3. The production process of a high tensile strength electrolytic copper foil according to claim 1, characterized in that: The current density during electrolytic foil making is 50~80A / dm 2 , the electrodeposition time is 100 to 180 s.

4. The production process of a high tensile strength electrolytic copper foil according to claim 1, characterized in that: The additive is an aqueous solution containing a surface improver, a nonionic surfactant, a smoothing agent and gelatin, wherein the concentration of the surface improver in the aqueous solution is 0.6-1 g / L, the concentration of the nonionic surfactant is 0.2-0.4 g / L, the concentration of the smoothing agent is 0.4-0.6 g / L, the concentration of the gelatin is 1.5-2 g / L, and the number average molecular weight of the gelatin is 1000-5000.

5. The production process of a high tensile strength electrolytic copper foil according to claim 4, characterized in that: The nonionic surfactant is selected from any one of the nonionic fluorinated surfactant F-6000 and the nonionic fluorinated surfactant FS-104.

6. The production process of a high tensile strength electrolytic copper foil according to claim 1, characterized in that: The flow rate of electrolyte during electrolytic foil making is 30-40m 3 / h, and the flow rate of the additive is 40-60mL / min.

7. The production process of a high tensile strength electrolytic copper foil according to claim 4, characterized in that: The preparation method of the appearance improving agent comprises the following steps: adding 3-ethoxy-4-hydroxybenzaldehyde into a 15-20wt% ethanol aqueous solution at a dosage ratio of 0.03-0.05g / mL, mixing and stirring evenly, heating to 40-60°C, then slowly dropping a reducing agent therein, heating to 80-85°C after uniform dispersion, and reacting at this temperature with stirring and keeping warm for 8-12h; after the reaction is completed, slowly dropping a cyclohexanehexol phosphate aqueous solution with a mass of 85-95% of 3-ethoxy-4-hydroxybenzaldehyde and a concentration of 20-40wt% into the obtained product components, mixing evenly, heating to 75-85°C, keeping warm for reaction for 3-5h, and naturally cooling to room temperature, thereby obtaining the appearance improving agent.

8. The production process of a high tensile strength electrolytic copper foil according to claim 7, characterized in that: The reducing agent is a saturated aqueous solution of sodium sulfite, and the amount thereof is 75-85% of the mass of 3-ethoxy-4-hydroxybenzaldehyde.

9. The production process of a high tensile strength electrolytic copper foil according to claim 4, characterized in that: The preparation method of the smoothing agent comprises the following steps: Step 1, placing a 2-3 mol / L 1,3-diaminoheterocyclopentadiene aqueous solution in a constant temperature water bath at 50-60° C., adding 1,6-di(2,3-epoxypropoxy)hexane in a molar amount of 0.7-1.0 times that of 1,3-diaminoheterocyclopentadiene dropwise therein while stirring, mixing and stirring for 30-40 minutes, then heating to 90-95° C., and keeping the temperature at this temperature for reaction for 15-25 hours; Step 2: After the reaction is completed, the reaction product is naturally cooled to 55-70° C., 1,2-oxathiohydroxyalkane-2,2-dioxide with a molar amount of 0.1-0.2 times that of 1,3-diaminocyclopentadiene is added, and the mixture is stirred and kept warm at 60-70° C. for 5-8 hours; after the reaction is completed, the resultant components are naturally cooled to room temperature, and then the pH is adjusted to 2.3-2.8 with 40-50wt% sulfuric acid, and the final product is a smoothing agent.

10. A high tensile strength electrolytic copper foil, characterized in that: The high tensile strength electrolytic copper foil is produced by the production process of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method for electrolytic copper foil

    CN110042438A